Microporation-Mediated Transdermal Delivery of In Situ Gel Incorporating Etodolac-Loaded PLGA Nanoparticles for Management of Rheumatoid Arthritis - Heba M. El Sorogy; Sahar M. Fayez; Islam A. Khalil; Gehad A. Abdel Jaleel; Ahmed M. Fayez; Hesham A. Eliwa; Hoda E. Teba (MDPI AG, 2024)
Management of rheumatoid arthritis (RA) requires long-term administration of different medications since there has been no cure until now. Etodolac (ETD) is a nonsteroidal anti-inflammatory drug commonly used for RA management. However, its long-term administration resulted in severe side effects. This study aimed to develop a transdermal in situ gel incorporating ETD-loaded polymeric nanoparticles (NPs) to target the affected joints for long-term management of RA. Several PLGA NPs incorporating 1% ETD were prepared by nanoprecipitation and optimized according to the central composite design. The optimum NPs (F1) exhibited 96.19 ± 2.31% EE, 282.3 ± 0.62 nm PS, 0.383 ± 0.04 PDI, and −6.44 ± 1.69 ZP. A hyaluronate coating was applied to F1 (H-F1) to target activated macrophages at inflammation sites. H-F1 exhibited 287.4 ± 4.2 nm PS, 0.267 ± 0.02 PDI, and −23.7 ± 3.77 ZP. Pluronic F-127 in situ gel (H-F1G) showed complete gelation at 29 °C within 5 min. ETD permeation from H-F1G was sustained over 48 h when applied to microporated skin and exhibited significant enhancement of all permeation parameters. Topical application of H-F1G (equivalent to 8 mg ETD) to Wistarrat microporated skin every 48 h resulted in antirheumatic therapeutic efficacy comparable to commercial oral tablets (10 mg/kg/day).